A Study on the Effectiveness of an Observation Checklist in Physical Education Class - FUKAMI, Eiichiro; TAKAHASHI, Takeo; IYODA, Satoru; HINO, Katsuhiro; HASEGAWA, Etsushi (Japanese Journal of Sport Education Studies, 1996)
The purpose of this study was to examine the effectiveness of an observation checklist in physical education class developed by Takahashi, T, et. al. The effectiveness was examined through analyzing the correlation between the observer's evaluation by the checklist and students' formative evaluation to the same class. As it was supposed that frequency of observation in physical education classes would make a difference in the observer's evaluation, analyses were also done according to attendance frequency at physical education classes open to the public. The subjects were 493 teachers who attended and observed the physical education classes (27) open to the public at 13 elementary schools. In these classes 881 students were instructed. Main findings were as follows: 1) As the result of a Factor Analysis, the same 5 factors as in the previous research were extracted; those were “interaction of teacher”, “learning environment”, “momentum of instruction”, “motivated learning” and “effective learning”. 2) Correlations between the checklist and the formative evaluations were significant, but these were not so high. 3) The higher correlations were recognized, when analyzed according to attendance frequency of observers. The evaluation of observers with infrequent experience showed low correlation with students' evaluation. However, the evaluation of experienced observers showed higher correlation. 4) These results suggest that the checklist is effective instrument for the experienced observer, but not for the less experienced observer. Thus, the less experienced observer needs a certain training before using it.